Construction of roof, interior shot looking at skylight, Janko, Dr. and Mrs. Albert, residential, Monterey (1977)
Caption on back reads: 'Tripod arch and dome along with draped bars and mesh in place. One sections of draped roof is being covered with concrete (3/4" thick).'